Implementation Of The Covid 19 Vaccine At The Royal Prima Marelan Hospital In 2022 - Natasha Rismayana Wijayanti; Sri Lestari Ramadhani Nasution; Ermi Girsang; Ali Napiah Nasution (International Journal of Health and Pharmaceutical (IJHP), 2022)
One of the most effective ways is the provision of vaccines for every Indonesian citizen. The implementation of the vaccination program aims to reduce the transmission/transmission of Covid-19, reduce morbidity and mortality due to Covid-19, achieve group immunity in the community (herd immunity) and protect the community from Covid-19. The purpose of this study is to implement the implementation of the Covid-19 vaccine at the Royal Marelan Hospital 2022. This type of research is a qualitative research with an analytical descriptive design. The data collection technique was carried out by conducting interviews with staff involved in the implementation of the Covid-19 vaccination stages 1, 2 and 3 regarding the evaluation process for the implementation of the Covid-19 vaccination starting from the planning stage, stages 1, 2 and 3. conducted by researchers on 12 officers involved in the Covid-19 vaccination program, information was obtained that the implementation of the Covid-19 Vaccine phase 1 at the Royal Prima Marelan Hospital in stages 1, 2 and 3 went well and achieved the targets set by the hospital. . The community has also greatly benefited from the implementation of the Covid-19 vaccine.